Agile practices adapted to mass‐market application development. Issue 9 (6th August 2014) - Heredia, Alberto; Garcia‐Guzman, Javier; Amescua‐Seco, Antonio; Velasco‐Diego, Manuel; Biró, M.; Messnarz, R.; Colomo‐Palacios, R.
ABSTRACT Mobile app markets have experienced a significant growth during the last year. The increasing number of apps available on markets and the profits that developers and companies obtain are relevant enough to seriously consider the way apps are developed. The always‐changing environment in which apps are produced makes agile a convenient methodology to follow. Although agile allows the development team to quickly adjust the requisites to the new customer's needs, there is a lack of research on how agile methodologies can be explicitly adapted to develop mass‐market applications. Many references explain how to design and code a mobile app, but there is not much knowledge about other stages in the development process. Adapting an agile methodology to the development of mass‐market applications would provide project teams with a clear guide to successfully produce an app without missing any step in the process. This paper describes a case study in which an agile mass‐market application development process is followed. The proposed process also considers marketing issues as they are necessary to publicize a mass‐market application. This process has been followed and refined for several years in the development of the institutional apps at Carlos III University of Madrid. Copyright © 2014 John Wiley & Sons, Ltd.